1969
DOI: 10.1128/jb.100.2.1128-1130.1969
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy of Effect of Polymyxin on Escherichia coli Lipopolysaccharide

Abstract: Polymxyin treatment of isolated lipopolysaccharide from Escherichia coli resulted in the breakdown of its structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…It has previously been shown that surface active agents such as sodium lauryl sulfate and sodium deoxycholate disaggregate the LPS (26,35). Polymyxin antibiotics also show similar effects on bacterial LPS as demonstrated by disappearance of endotoxic activity (36) and the disruption of the membrane-like structure typical of LPS (23). Polymyxin B also liberates the periplasmic penicillinase of GI Ila I without any concomitant release of ,B-galactosidase (42).…”
Section: Resultsmentioning
confidence: 88%
“…It has previously been shown that surface active agents such as sodium lauryl sulfate and sodium deoxycholate disaggregate the LPS (26,35). Polymyxin antibiotics also show similar effects on bacterial LPS as demonstrated by disappearance of endotoxic activity (36) and the disruption of the membrane-like structure typical of LPS (23). Polymyxin B also liberates the periplasmic penicillinase of GI Ila I without any concomitant release of ,B-galactosidase (42).…”
Section: Resultsmentioning
confidence: 88%
“…The electron microscopic examination of uranyl formate stained LPS from S. typhimurium strain 7 (12) and E. coli 018 (23) showed a ribbon-like structure (fila- mentous form) with branching, whereas, LPS from S. typhimurium stained with ammonium molybdate showed a spherical structure (19). Ribi et al (18) and Lopes and Innes (13) reported that LPS isolated from S. enteritidis S-795 and E. colt 018, respectively, appeared as branching ribbons when stained with phosphotungstate and tungstate.…”
Section: Discussionmentioning
confidence: 99%
“…The precise nature of the interaction of PB with LPS and its haptenated derivative is unknown, although work on model membrane systems and the selective toxicity of PB for gram-negative bacteria suggest that the presence of phosphatidylethanolamine in the LPS of bacterial cell walls is important (11)(12)(13)(14)(15)(16)(17)Footnote 1) . An interaction might also be expected between the highly charged PB, which contains five y-amino groups, and the phosphate groups of LPS .…”
Section: Discussion and Summarymentioning
confidence: 99%